Magnus Schwantje, die Ethische Rundschau und die Tierschutzfrage - Philippe Alexandre (Recherches Germaniques)
Pacifist Magnus Schwantje (1877-1959) was also a campaigner for animal rights. Respect for life and compassion for animals were the grounds for his action against animal cruelty. In 1912 he founded the Society for the Empowerment of Animal Protection and Related Issues. This Society published a journal called Ethische Rundschau (Ethical Review) to enlighten public opinion about its ideas and the ethical reasons for fighting against every kind of animal abuse. This movement recognised animals as ‘sentient beings’. Such a radical ethics implied criticism of hunting, vivisection and common slaughterhouse practices, the adoption of another way of life (vegetarianism), new rules for life and measures to educate young people to this ethics.